Physiologic flow-conditioning limits vascular dysfunction in engineered human capillaries. (January 2022) - Haase, Kristina; Piatti, Filippo; Marcano, Minerva; Shin, Yoojin; Visone, Roberta; Redaelli, Alberto; Rasponi, Marco; Kamm, Roger D.
Abstract: Hemodynamics play a central role in the health and disease of the coronary and peripheral vascular systems. Vessel-lining endothelial cells are known mechanosensors, responding to disturbances in flow – with mechanosensitivity hypothesized to change in response to metabolic demands. The health of our smallest microvessels have been lauded as a prognostic marker for cardiovascular health. Yet, despite numerous animal models, studying these small vessels has proved difficult. Microfluidic technologies have allowed a number of 3D vascular models to be developed and used to investigate human vessels. Here, two such systems are employed for examining 1) interstitial flow effects on neo-vessel formation, and 2) the effects of flow-conditioning on vascular remodeling following sustained static culture. Interstitial flow is shown to enhance early vessel formation via significant remodeling of vessels and interconnected tight junctions of the endothelium. In formed vessels, continuous flow maintains a stable vascular diameter and causes significant remodeling, contrasting the continued anti-angiogenic decline of statically cultured vessels. This study is the first to couple complex 3D computational flow distributions and microvessel remodeling from microvessels grown on-chip (exposed to flow or no-flow conditions). Flow-conditioned vessels (WSS < 1Pa for 30 μm vessels) increase endothelial barrier function, result in significant changes in gene expression and reduce reactive oxygen species and anti-angiogenic cytokines. Taken together, these results demonstrate microvessel mechanosensitivity to flow-conditioning, which limits deleterious vessel regression in vitro, and could have implications for future modeling of reperfusion/no-flow conditions.